Effects of Different Inspiratory Muscle Training Protocols on Exercise Capacity, Respiratory Muscle Strength, and Health-Related Quality of Life in Patients with Hypertension - İrem Hüzmeli; Nihan Katayıfçı; Fatih Yalçın; Esra Doğru Hüzmeli (International Journal of Clinical Practice)
Aim. This study aimed to explore how varying inspiratory muscle training workloads affect exercise capacity, health-related quality of life (HrQoL), depression, peripheral and respiratory muscle strength, pulmonary function, dyspnea, fatigue, and physical activity levels in hypertension (HT) patients. Methods. A randomized, controlled three-arm study. Forty-five patients (58.37 ± 8.53 y, 7F/38M) with HT received IMT (7 days/8 weeks) by POWERbreathe® Classic LR device and were randomized to control group (CG, 10% maximal inspiratory pressure (MIP), n: 15), low-load group (LLG, 30% MIP), and high-load group (HLG, %50 MIP). Exercise capacity, HrQoL, depression, peripheral and respiratory muscle strength, pulmonary function, fatigue, physical activity level, dyspnea, and sleep quality were evaluated before and after the training. Results. Exercise capacity, physical functioning, peripheral muscle strength, and resting dyspnea were statistically significantly improved in HLG and LLG after the training compared to CG p<0.05. Similar improvements in perception of depression, fatigue, and sleep quality were seen within and between the groups p>0.05. Statistically significant differences were found within all the groups in terms of MIP and PEF values of respiratory functions p<0.05. The superior improvement in the physical activity level was found in the HLG p<0.05. Discussion. High-load IMT was particularly effective in increasing physical activity level, peripheral muscle strength, exercise capacity, and improved HrQoL. Low-load IMT was effective in reducing dyspnea and improving respiratory function. Device-guided breathing exercises decreased blood pressure, improved sleep quality, and strengthened respiratory muscles. IMT, an efficient method, is suggested for inclusion in rehabilitation programs due to its capacity to increase physical activity, exercise capacity, and peripheral muscle strength, enhance HrQoL and respiratory function, and alleviate dyspnea. Also, the efficacy of IMT should be investigated with different training protocols such as endurance IMT or functional IMT in HT patients.